2001
DOI: 10.4049/jimmunol.166.12.7437
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic Immunity to Influenza A Virus in Mice Lacking IgA, All Ig, NKT Cells, or γδ T Cells

Abstract: The mechanisms of broad cross-protection to influenza viruses of different subtypes, termed heterosubtypic immunity, remain incompletely understood. We used knockout mouse strains to examine the potential for heterosubtypic immunity in mice lacking IgA, all Ig and B cells, NKT cells (CD1 knockout mice), or γδ T cells. Mice were immunized with live influenza A virus and compared with controls immunized with unrelated influenza B virus. IgA−/− mice survived full respiratory tract challenge with heterosubtypic vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 68 publications
3
99
0
Order By: Relevance
“…TCID 50 assays were performed as described in ref. 30. Briefly, lung homogenates or tissue culture supernatants were assayed for virus infectivity on MDCK by endpoint dilution for cytopathic effect with a 10-fold dilution series.…”
Section: Methodsmentioning
confidence: 99%
“…TCID 50 assays were performed as described in ref. 30. Briefly, lung homogenates or tissue culture supernatants were assayed for virus infectivity on MDCK by endpoint dilution for cytopathic effect with a 10-fold dilution series.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) was performed as described previously (15) on plates coated with lysates of influenza virus–infected cells. Hemagglutination inhibition (HI) was performed by standard methods with sera pretreated with receptor-destroying enzyme (36).…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have demonstrated potent and long-lasting heterosubtypic immunity, that is, exposure to a virus of one subtype protects against challenge infection with another subtype (10–15). The mechanisms of heterosubtypic immunity are not completely understood but likely include both T-cell immunity, in particular CD8+ cytotoxic T-lymphocytes (CTL) (16,17) and CD4+ T cells (13), as well as antibodies to conserved epitopes (18).…”
mentioning
confidence: 99%
“…Total IgG titers were determined by ELISA against lysates of PR8-infected MDCK cells as described previously (32).…”
mentioning
confidence: 99%